Rectal Shaving in Colorectal Endometriosis Surgery—Definition, Evidence and Variability - Petya Tanovska; Jörg Keckstein; Mihai Constantin; Maya Sophie de Wilde; Petra Klein; Harald Krentel (Journal of Clinical Medicine, 2026)
Objectives: We aim to evaluate how rectal shaving is defined in the current literature, how consistently this definition is used, and what this means for the results and comparability of the respective research about surgery in deep rectal endometriosis. Methods: A literature search was performed in PubMed covering the period from 1990 to 2026, using multiple search terms combining “rectal shaving”, “shaving”, “conservative surgery” and “endometriosis”. Records were screened by title and abstract; methods sections of eligible publications were examined in full text, where accessible, to assess whether an explicit, anatomically anchored definition of rectal shaving (depth of excision, mucosal status, and bowel lumen involvement) was provided, benchmarked against the 2021 international consensus terminology. Information on definitions of rectal shaving, recurrence, and complication outcomes was extracted and compared. Outcomes: The review focused on how rectal shaving is defined, how variable the definition is used, and what this means for comparability of study results on recurrence and complication rates reported in the literature. Results: In studies using the term rectal shaving, the definitions of what rectal shaving means varied widely, ranging from superficial removal of serosa to full-thickness excision of the rectal muscular layer and the opening of the bowel lumen. This heterogeneity makes direct comparison of published literature difficult. Only a minority of publications provided a sufficiently explicit, anatomically anchored definition. Recurrence rates seem to be higher in patients with superficial excision compared to more radical resection, although this comparison is based on heterogeneous, predominantly observational data with inconsistent recurrence definitions, whereas complication rates are consistently lower in less radical surgeries. Conclusions: Definitions of rectal shaving in deep rectal endometriosis surgery are inconsistent in the available literature. This limits comparability of results regarding complication and recurrence rates. Future studies should clearly differentiate between superficial and deep excision of the muscularis layer, specifying whether mucosal integrity is preserved and whether suturing is required, and should explicitly reference standardized consensus terminology where available.